Preparation of Coconut Milk as Dandruff Removal - Marini Damanik; Hafni Indriati Nasution; Rini Selly; Moondra Zubir (Indonesian Journal of Chemical Science and Technology (IJCST), 2020)
Coconut milk is a thick white liquid extracted from coconut produced from shredded coconut and then squeezed with water. Coconut milk is an ingredient produced from processed old coconut. Coconut milk can be used as food preparations or as herbal beauty ingredients. One of the advantages of coconut milk in the field of beauty is that it is very effective as a dandruff remover. By using old coconut milk as a dandruff remover we can get amazing results with natural ingredients without spending a lot of money. Coconut milk has many contents such as water content, protein and fat which are quite high as well as cow's milk. Coconut milk is rich in vitamins C, B, B-6, thiamine, niacin, folate, a number of minerals (calcium, magnesium, iron and phosphorus). Pure coconut milk only contains 54 percent water, 35 percent fat and 11 percent nonfat solids (approximately 6 percent carbohydrates, less than 4 percent protein and other solids) which are categorized as emulsions of oil in water. Coconut milk is known to be effective in eliminating dandruff, because coconut milk contains coconut oil containing Vitramin E and fatty acids that can eliminate and eradicate dandruff. You do this by using coconut oil as a massage oil to massage the scalp.